NMDA receptor blockade reduces TMJ-evoked activity of trigeminal subnucleus caudalis neurons in an estrogen-dependent manner - Tashiro, A. (2009)
Estrogen status is a risk factor in painful temporomandibular disorders (TMJD). Previously we reported that estradiol (E2) enhanced nociceptive processing of TMJ input by neurons in superficial laminae at the spinomedullary (Vc/C(1-2)) region; however, the mechanisms for this enhancement are not known. The present study determined if ionotropic glutamate receptors contribute to TMJ nociceptive processing in an E2-dependent manner. Ovariectomized (OvX) female rats were treated with high E2 (HE2) or low dose E2 (LE2) for 2 days and neural activity was recorded in laminae I-II at the Vc/C(1-2) region. TMJ-responsive units were activated by adenosine triphosphate (ATP) injections into the joint space. ATP-evoked unit responses in HE2 rats were reduced significantly by topical application of the N-methyl-D-aspartate receptor antagonist, D(−) -2-amino-5-phosphonopentanoic acid (AP5) in a dose-related manner, while units from LE2 were not affected. Application of the non-NMDA receptor antagonist, 6,7-dinitroquinoxaline-2,3-dione (DNQX), inhibited the ATP-evoked responses in both groups. Spontaneous activity of TMJ units was not influenced by AP5, whereas it was reduced by DNQX similarly in both groups. The high threshold convergent cutaneous receptive field area of TMJ units was not changed by AP5, whereas DNQX caused a significant reduction in both groups. These results suggest that NMDA-dependent mechanisms contribute to the enhanced ATP-evoked responses of TMJ units in superficial laminae at the Vc/C(1-2) region under high E2 conditions, while non-NMDA-dependent mechanisms modify the encoding properties of TMJ units independent of E2 status.